Transparency in Ecology and Evolution: Real Problems, Real Solutions. (September 2016) - Parker, Timothy H.; Forstmeier, Wolfgang; Koricheva, Julia; Fidler, Fiona; Hadfield, Jarrod D.; Chee, Yung En; Kelly, Clint D.; Gurevitch, Jessica; Nakagawa, Shinichi
Abstract : To make progress scientists need to know what other researchers have found and how they found it. However, transparency is often insufficient across much of ecology and evolution. Researchers often fail to report results and methods in detail sufficient to permit interpretation and meta-analysis, and many results go entirely unreported. Further, these unreported results are often a biased subset. Thus the conclusions we can draw from the published literature are themselves often biased and sometimes might be entirely incorrect. Fortunately there is a movement across empirical disciplines, and now within ecology and evolution, to shape editorial policies to better promote transparency. This can be done by either requiring more disclosure by scientists or by developing incentives to encourage disclosure. Trends: Evidence suggests that insufficient transparency is a problem across much of ecology and evolution. Results and methods are often reported in insufficient detail or go entirely unreported. Further, these unreported results are often a biased subset, thus substantially hampering interpretation and meta-analysis. Journals and other institutions, such as funding agencies, influence researchers' decisions about disseminating results. There is a movement across empirical disciplines, including ecology and evolution, to shape institutional policies to better promote transparency. Institutions can promote transparency by requiring or encouraging more disclosure, as with the now-familiar data archiving, or by developing an incentive structure promoting disclosure, such as preregistration of studies and analysis plans.